Analysing human nails composition by using laser induced breakdown spectroscopy - Hanin Athirah Harun; Roslinda Zainal; Yaacob Mat Daud (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study investigated the elemental composition of pathological and normal nails, according to different age groups and genders. The nail elemental composition was analyzed by using Laser Induced Breakdown Spectroscopy (LIBS) technique. A Q-switched Nd:YAG laser at 1064 nm with output energy of 100 mJ, pulse duration of 6 ns and repetition rate of 1 Hz was fired to the human nails sample. The laser pulse ablated the target sample surface and produced plasma plume with characteristic spectral line comprising sample’s elemental composition. The plasma emission spectrum of nail samples were captured by fibre optic detection device and spectrometer equipped with ASEQ Spectra Software for elemental analysis. The elements detected in nails were Mg, Al, Ca, P, Ti, K and Na. Classification of nails into different age groups and genders demonstrate efficient results if compared with Dietary Reference Intakes (DRI). The results indicate that Ca, Al, Ti, P and K composition were higher among female. However, Mg and Na were higher among male. The results also show that Ca and K element decline as the age increase in both genders. The pathological nails’ elemental compositions were also noticeably related to the nail disorder condition itself. It is proven that LIBS could be a possible method for analyzing the nails and identification of various nail disorders.